18F-FDG PET/CT Demonstrating Malignant Degeneration of a Uterine Fibroid. (October 2016) - Sharma, Punit
Abstract : Abstract: Whereas benign leiomyoma of the uterus (fibroid) is very common, malignant degeneration of such fibroids to leiomyosarcoma is rare. Anatomical imaging with CT or MRI cannot differentiate between larger leiomyoma and leiomyosarcoma. Imaging with 18 F-FDG PET/CT can be helpful in differentiating the two. High-grade 18 F-FDG uptake in uterine fibroids is suspected and warrants surgical excision for further evaluation. We present such as case of a 42-year-old premenopausal woman where 18 F-FDG PET/CT helped in making the diagnosis of malignant degeneration of uterine fibroid.